Sustainable thermoplastic elastomers derived from plant oil and their "click-coupling" via TAD chemistry1. Issue 7 (6th July 2015) - Wang, Zhongkai; Yuan, Liang; Trenor, Nathan M.; Vlaminck, Laetitia; Billiet, Stijn; Sarkar, Amrita; Du Prez, Filip E.; Stefik, Morgan; Tang, Chuanbing
<x xml:space="preserve">Abstract</x> We report the preparation of plant oil based triblock copolymers as thermoplastic elastomers with the aid of TAD chemistry.